Microwaves effectively examine the extent and type of coking over acid zeolite catalysts - Liu, B; Slocombe, DR; Wang, J; Aldawsari, A; Gonzalez-Cortes, S; Arden, J; Kuznetsov, VL; AlMegren, H; AlKinany, M; Xiao, T; Edwards, PP (Springer Nature, 2017)
Coking leads to the deactivation of solid acid catalyst. This phenomenon is a ubiquitous problem in the modern petrochemical and energy transformation industries. Here, we show a method based on microwave cavity perturbation analysis for an effective examination of both the amount and the chemical composition of cokes formed over acid zeolite catalysts. The employed microwave cavity can rapidly and non-intrusively measure the catalytically coked zeolites with sample full body penetration. The overall coke amount is reflected by the obtained dielectric loss (ε″) value, where different coke compositions lead to dramatically different absorption efficiencies (ε″/cokes' wt%). The deeper-dehydrogenated coke compounds (e.g., polyaromatics) lead to an apparently higher ε″/wt% value thus can be effectively separated from lightly coked compounds. The measurement is based on the nature of coke formation during catalytic reactions, from saturated status (e.g., aliphatic) to graphitized status (e.g., polyaromatics), with more delocalized electrons obtained for enhanced Maxwell-Wagner polarization.Catalyst deactivation by coke deposition is a major drawback in industrial processes. Here, the authors show a non-intrusive microwave cavity perturbation technique as a powerful tool to determine the nature and extent of coke accumulation in industrially-relevant zeolite catalysts.